In Vitro Activity of Essential Oils against Saprolegnia parasitica - Simona Nardoni; Basma Najar; Baldassare Fronte; Luisa Pistelli; Francesca Mancianti (Molecules, 2019)
Saprolegnia spp. water molds severely impact fish health in aquaculture, fish farms and hobby fish tanks colonizing mature and immature stages of fishes, as well as eggs. Considering that there are no drugs licensed for treating and/or control the organism, efficient and environmental low-impact methods to control these oomycetes in aquaculture are needed. The aim of the present report was to evaluate the in vitro sensitivity of Saprolegnia parasitica to essential oils (EOs) from Citrus aurantium L., Citrus bergamia Risso et Poiteau, Citrus limon Burm. f., Citrus paradisi Macfad, Citrus sinensis Osbeck, Cinnamomum zeylanicum Blume, Cymbopogon flexuosum (Nees ex Steud.) Watson, Foeniculum vulgare Mill., Illicium verum Hook.f., Litsea cubeba (Lour.) Pers., Origanum majorana L., Origanum vulgare L., Pelargonium graveolens L’Hér., Syzygium aromaticum Merr. & L.M.Perry, and Thymus vulgaris L., by microdilution test. The most effective EOs assayed were T. vulgaris and O. vulgare, followed by C. flexuosum, L. cubeba and C. bergamia. These EOs could be of interest for controlling Saprolegnia infections. Nevertheless, further safety studies are necessary to evaluate if these products could be dispersed in tank waters, or if their use should be limited to aquaculture supplies.